2020
DOI: 10.3389/fpsyg.2020.00618
|View full text |Cite
|
Sign up to set email alerts
|

Structural Equation Modeling of Vocabulary Size and Depth Using Conventional and Bayesian Methods

Abstract: In classifications of vocabulary knowledge, vocabulary size and depth have often been separately conceptualized (Schmitt, 2014). Although size and depth are known to be substantially correlated, it is not clear whether they are a single construct or two separate components of vocabulary knowledge (Yanagisawa and Webb, 2020). This issue has not been addressed extensively in the literature and can be better examined using structural equation modeling (SEM), with measurement error modeled separately from the cons… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
21
2
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(26 citation statements)
references
References 82 publications
1
21
2
1
Order By: Relevance
“…In addition, employing CFA methodologies, Kremmel et al (2017) found that an L2 phraseological-knowledge factor correlated at .90 with a general vocabulary factor while measuring different word sets. Similarly, Koizumi and In'nami (2020) found a striking correlation of .94-.95 between an L2 form-meaning link factor and a depth factor comprised of polysemy, collocations, and associations. The unidimensional model revealed in the current study provides evidence that the word-knowledge aspects do not behave as entirely separable entities and explains why the correlations exhibited by much previous research are so high that they can barely distinguish the lexical aspects.…”
Section: Empirical Unidimensionality Of Vocabulary Knowledgementioning
confidence: 87%
See 1 more Smart Citation
“…In addition, employing CFA methodologies, Kremmel et al (2017) found that an L2 phraseological-knowledge factor correlated at .90 with a general vocabulary factor while measuring different word sets. Similarly, Koizumi and In'nami (2020) found a striking correlation of .94-.95 between an L2 form-meaning link factor and a depth factor comprised of polysemy, collocations, and associations. The unidimensional model revealed in the current study provides evidence that the word-knowledge aspects do not behave as entirely separable entities and explains why the correlations exhibited by much previous research are so high that they can barely distinguish the lexical aspects.…”
Section: Empirical Unidimensionality Of Vocabulary Knowledgementioning
confidence: 87%
“…In a related study, Koizumi and In'nami (2020) investigated the factor structure of vocabulary knowledge, understood as the combination of size (form-meaning link) and depth (polysemy, collocation, and word association) of knowledge, in Japanese L2 English learners. As in Kieffer and Lesaux (2012), the study employed readily available written tests designed for a different research purpose and, thus, each task measured distinct target words across each word-knowledge component.…”
Section: The Nature Of Vocabulary Knowledgementioning
confidence: 99%
“…This may indicate that some of the headwords from lower frequency word families in the test were unknown to the EFL undergraduate students, making the test more challenging for them. Research has shown that vocabulary size and depth of vocabulary knowledge are closely related (González‐Fernández & Schmitt, 2020; Koizumi & In’nami, 2020). Given that receptive affix knowledge and vocabulary size are likely to be closely related to each other (Mochizuki & Aizawa, 2000), future research should directly investigate the effect of vocabulary size on productive knowledge of derivatives.…”
Section: Discussionmentioning
confidence: 99%
“…In a recent study, Vafaee and Suzuki (2020) found that although the correlation is not weak between vocabulary size and depth, they are separate constructs. Likewise, Koizumi and In'nami (2020), using both conventional and Bayesian SEM, reported a strong correlation between them, but identified them to be separate constructs. In the main, although teasing them apart as two separate constructs may be virtually difficult, it is safe to say that their inclusion results in a more accurate measurement of the vocabulary construct (Vafaee & Suzuki, 2020).…”
Section: Vocabulary Knowledge: Depth and Breadth Aspectsmentioning
confidence: 99%